An aromatic amino acid and associated helix in the C-terminus of the potato leafroll virus minor capsid protein regulate systemic infection and symptom expression. - Yi Xu; Washington Luis Da Silva; Yajuan Qian; Stewart M Gray (PLoS Pathogens, 2018)
The C-terminal region of the minor structural protein of potato leafroll virus (PLRV), known as the readthrough protein (RTP), is involved in efficient virus movement, tissue tropism and symptom development. Analysis of numerous C-terminal deletions identified a five-amino acid motif that is required for RTP function. A PLRV mutant expressing RTP with these five amino acids deleted (Δ5aa-RTP) was compromised in systemic infection and symptom expression. Although the Δ5aa-RTP mutant was able to move long distance, limited infection foci were observed in systemically infected leaves suggesting that these five amino acids regulate virus phloem loading in the inoculated leaves and/or unloading into the systemically infected tissues. The 5aa deletion did not alter the efficiency of RTP translation, nor impair RTP self-interaction or its interaction with P17, the virus movement protein. However, the deletion did alter the subcellular localization of RTP. When co-expressed with a PLRV infectious clone, a GFP tagged wild-type RTP was localized to discontinuous punctate spots along the cell periphery and was associated with plasmodesmata, although localization was dependent upon the developmental stage of the plant tissue. In contrast, the Δ5aa-RTP-GFP aggregated in the cytoplasm. Structural modeling indicated that the 5aa deletion would be expected to perturb an α-helix motif. Two of 30 plants infected with Δ5aa-RTP developed a wild-type virus infection phenotype ten weeks post-inoculation. Analysis of the virus population in these plants by deep sequencing identified a duplication of sequences adjacent to the deletion that were predicted to restore the α-helix motif. The subcellular distribution of the RTP is regulated by the 5-aa motif which is under strong selection pressure and in turn contributes to the efficient long distance movement of the virus and the induction of systemic symptoms.